The Influence of the Halal Label on the Decision to Buy Kripik Ahsan 96 in Donomulyo - Agus Wicahyono (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine and analyze the effect of the halal label on purchasing decisions for ahsan 96 chips in Donomulyo. This research is a descriptive research with a quantitative approach. The population that became the sample of this study were customers who bought 96 ahsan chips at Donomulyo. The questionnaire was tested with a reliability test using Alpha Crombach and tested for validity using the Pearson correlation test. The data analysis technique used in this study was simple linear regression with primary data processing using the Statistical Package for Social Science (SPSS) version 21. The results showed that the halal label had a positive effect on purchasing decisions for ahsan 96 chips at Donomulyo. This can be shown from the results of the R2 test, the result is 0.249, if the percentage of the influence of halal variables on purchasing decisions for ahsan 96 chips in Donomulyo is 24.9% and 75.1% is influenced by variables that are not in this study. The results of the t test obtained t count > t table (df = 60-2) with a result of 4.389 > 2.001 so that it can be said that there is a positive influence of the halal label on purchasing decisions for ahsan 96 chips in Donomulyo which implies that purchasing decisions can be influenced by halal labels, although there are other factors not present in this study that could influence the results